Asperger syndrome and psychotherapy : understanding asperger perspectives - Jacobsen, Paula (Jessica Kingsley, 2003)
People with Asperger Syndrome (AS) understand and respond to the world in a very different way from people without this condition. The challenge for psychotherapists working with Asperger clients lies in setting aside their own preconceptions and learning to understand their client's perspective. Behaviour that, in a ''neurotypical'' client, may be evidence of a problem, in an Asperger client may simply be a manifestation of Asperger ways of approaching the world. Paula Jacobsen, an experienced child psychotherapist, demonstrates how to interpret classic analytic and psychodynamic theories in.